Distribution of interactional metadiscourse markers in creative arts journal papers - Noor Afifah, Nawawi; Ting, Su Hie (2022)
Interactional metadiscourse markers assist writers in managing their relationship with their readers. Interactional markers allow researchers to interject their research reports with their views and provide commentaries on their content. For instance, hedges (e.g., “might”) reduce writers’ commitment towards a claim, boosters (e.g., “clearly”) emphasise the certainty of an argument, attitude markers (e.g., “surprisingly”) signal the writers’ attitude, self-mentions (e.g., “we”) allow writers to reveal their authorial self and engagement markers (e.g., “consider”) get readers involved into the conversation. These markers are useful especially in research articles as the formal use of language inhibit the relationship between a writer and their readers. Past studies have examined the use of interactional metadiscourse markers in research articles, covering various academic fields but little is known about how creative arts writers utilise interactional metadiscourse markers in various sections of the journal papers. Therefore, the descriptive study examined the usage of interactional markers in creative arts journal papers. The specific aspects focussed on are: (1) frequencies of the five categories of interactional markers; and (2) the distribution of interactional markers in the rhetorical sections of the journal papers. The corpus of the study comprised 20 journal papers from four Quartile 1-ranked journals in the SCOPUS database. The four journals were Cultural Trends, Fashion Theory, Empirical Studies of the Arts and Visual Communication. Articles retrieved from the journals cover general areas of visual and performing arts. These journal papers were chosen as they fit the selection criteria, which were: (1) journal papers that were published between the years of 2011 and 2021, and (2) journal papers that were organised into rhetorical sections like abstract, introduction, method, results, discussion, and conclusion. The journal papers were coded using an adapted version of Hyland’s (2005) interpersonal model. The results were organised based on the rhetorical sections: abstract, introduction, method and result-discussion-conclusion sections. A total of 3,994 interactional markers were identified in the 20 creative arts journal papers. The most frequently used marker was hedges (36.25%), followed closely by boosters (31.60%). In comparison, self-mention (13.55%), attitude marker (12.22%) and engagement markers (6.38%). The same distribution patterns were observed in the introduction section but the other rhetorical sections had different patterns. In the abstract section, boosters was the most frequently used marker, then hedges, self-mention, attitude markers and engagement markers. Next, in the method section, self-mentions occupied the top position, followed by hedges and boosters, and attitude markers and engagement markers were again the two least frequently used markers. Lastly, the result-discussion-conclusion sections had hedges as the most frequently used marker, followed by boosters and attitude markers but the two least frequently used markers were self-mention and engagement markers. A comparison of the results across rhetorical sections of journal papers show that hedges and boosters were the most frequently used markers in all the sections except the method section. The constant use of the two interactional markers reflects the writers’ awareness in controlling the strength of their argument as well as allowing alternative views to their propositional content. Aside from that, the results showed that the writers generally used more self-mentions than attitude markers in all of the rhetorical sections (except the result-discussion-conclusion sections). The more frequent use of self-mentions in the rhetorical sections, particularly in the method section, indicate that the creative arts writers tended to referred to themselves more than expressing their attitudes towards the propositional content. Notably, engagement markers was consistently the least used marker in all of the rhetorical sections in the creative arts journal papers analysed. The infrequent usage of engagement markers implies that the researchers placed low priority on building rapport with their readers. Another possible interpretation is that the creative arts researchers do not view journal papers as an appropriate space for reader engagement. This finding is expected as previous studies have also recorded infrequent use of engagement markers in journal papers. As mentioned earlier, the method section has self-mention as the most frequently used marker. This can be attributed to the researchers’ tendency of using first person pronouns when describing their research procedure. Arguably, as the method section leans more towards explanation rather than argumentation, the writers would find greater use for self-mentions than boosters. Similarly, in the result-discussion-conclusion sections the frequency of attitude markers was higher than self-mentions. As the result-discussion-conclusion sections require the creative arts researchers to be more evaluative when presenting and interpreting results, it would make sense that the usage of attitude markers would be more frequent there. Additionally, this could also explain why the distribution pattern of hedges and boosters is similar in the abstract, introduction and the result-discussion-conclusion sections. Compared to the method section, the aforementioned sections typically require writers to be assertive, provide justification as well as convey subjectivity. Thus, the frequent use of hedges and boosters. This study shows that the different functional purposes of the rhetorical sections influenced the researchers’ usage of interactional markers in journal papers, and this is an insightful finding made available because of the analysis of markers by rhetorical section. When the usage of interactional markers in creative arts journal papers is seen as a whole, hedges and boosters together account for two-thirds of the total number of interactional markers used. This is similar to Nawawi and Ting’s (2021) findings on political science journal papers but there is a major difference in that creative arts researchers are more inclined towards using hedges to reduce their commitment to claims, indicative of disciplinary differences in managing the relationship with their readers in journal papers. Keywords: interactional, metadiscourse, creative arts, research articles, journal paper